Best Practice in Early Childhood Development Financial Governance: A Case Study in Indonesia Villages - Indrawati, Retno; Komara Ragamustari, Safendrri; Ery Wijaya, Muhammad (JPUD - Jurnal Pendidikan Usia Dini, 2021)
Early childhood development (PAUD) is a fundamental investment that is included in the Sustainable Development Goals (SDGs). Previous research has shown that ECD investment in Indonesia, and its financial governance remains a challenging issue. Through a qualitative approach to a case study method design, this study aims to examine the state of PAUD financial management in Panggungharjo Village, Yogyakarta. This study uses in-depth interviews and desk research as data collection techniques. The instrument was developed from the SABER-ECD World Bank Assessment and ECD Financial Profiling Tools. The results showed that PAUD financial management in established villages had innovative financing, budget management and institutional development resulted in a blueprint for managing PAUD financing in other villages in Indonesia. Important policy objectives in all aspects, including the legal framework, cross-sectoral coordination, program coverage, coverage, equity, data availability, quality standards, and compliance with standards, the vision of financing early childhood development will be more achievable for future research. Keywords: Early Childhood, Financial Governance, Village References: Alatas, H., Brinkman, S., Chang, M. C., Hadiyati, T., Hartono, D., Hasan, A., Hyson, M., Jung, H., Kinnell, A., Pradhan, M., & Roesli, R. (2013). Early childhood education and development services in Indonesia. In Education in Indonesia (pp. 82–108). Institute of Southeast Asian Studies. Ambang.Yudanto. (2019). Analisis Kepemimpinan Transformasional Kepala Desa dalam Pengelolaan Badan Usaha Milik Desa: Studi Kasus Bumdes Panggung Lestari, Bantul [Analysis of Village Head Transformational Leadership in Village Owned Enterprise Management: A Case Study of Bumdes Panggung Lestari, Bantul]. The Journal of Business and Management. Antlöv, H., Wetterberg, A., & Dharmawan, L. (2016). Village Governance, Community Life, and the 2014 Village Law in Indonesia. Bulletin of Indonesian Economic Studies, 52(2), 161–183. https://doi.org/10.1080/00074918.2015.1129047 Aqsati, F. A. (2018). Pengelolaan Alokasi Dana Desa untuk Pengembangan Pembedayaan Masyarakat di Desa Panggungharjo [Management of Village Fund Allocation for Community Empowerment Development in Panggungharjo Village]. Resolusi: Jurnal Sosial Politik. Astuti, S. J. W., & Suaedi, F. (2019). Building Independent Villages through Collaborative Governance by Village-Owned Enterprises (Best Practice from Panggungharjo Village, Central Java, Indonesia). Iapa Proceedings Conference, 265. https://doi.org/10.30589/proceedings.2018.200 Basuki, A. F., Setyowati, K., & Wahyunengseh, R. D. (2019). Accountability Model of Financial Management in the Public Sector: A Study on Panggungharjo Village Budget. Bisnis & Birokrasi Journal. https://doi.org/10.20476/jbb.v26i1.10312 Bauhr, M., & Nasiritousi, N. (2013). Resisting Transparency: Corruption, Legitimacy, and the Quality of Global Environmental Policies. Global Environmental Politics, 13(August), 46–64. https://doi.org/10.1162/GLEP Bloom, N., Van Reenen, J., & Williams, H. (2019). A toolkit of policies to promote innovation. Voprosy Ekonomiki, 2019(10), 5–31. https://doi.org/10.32609/0042-8736-2019-10-5-31 Boggild-Jones, I., Gardiner, S., Gustafsson-Wright, E., Castillo, A. M., Castro Espinosa, B., Sánchez Vázquez, G., Rivera Ruíz, M., Hetzel, O., Lugo, H., Khan, A., Mozambique, F., Duarte, S., Fisker, A., Mozambique, A., Briggs, C., Kasajja, M.-S., Anis, K., Campira, P., Figia, N., … Njoroge, S. (2017). Emily Gustafsson-Wright the Standardized Early Childhood Development Costing Tool (SECT) A Global Good to Increase and Improve Investments in Young Children. Brinkman, S. A., Hasan, A., Jung, H., Kinnell, A., & Pradhan, M. (2017). The impact of expanding access to early childhood education services in rural Indonesia. Journal of Labor Economics, 35(S1), S305–S335. https://doi.org/10.1086/691278 Britto, P. R., Engle, P. L., & Super, C. M. (2013). Handbook of Early Childhood Development Research and Its Impact on Global Policy. In Handbook of Early Childhood Development Research and Its Impact on Global Policy. https://doi.org/10.1093/acprof:oso/9780199922994.001.0001 Cardenas, M., & Cadena, A. M. (2020). How to prioritize Early Childhood? A note on the recent expeerience in Columbia. May 2020. Denboba, A., Hasan, A., & Wodon, Q. (2015). Early Childhood Education and Development in Indonesia. In World Bank Publications. Edi, A. C., & Wardhani, I. S. (2019). Transformational and Transactional Leadership, Understanding How Leadership Cultivates Democratic Citizenship in Panggungharjo, Bantul, Yogyakarta. PCD Journal, 6(2), 239. https://doi.org/10.22146/pcd.35229 Hasan, Amer., Hyson, Marilou., & Chu-Chang, M. (2013). Early childhood education and development in poor villages of Indonesia: Strong foundations, later success. World Bank. Istiqomah, L. (2016). Tiga Pilar Kebijakan Pemerintah dalam Pembinaan PAUD. Golden Age [Three Pillars of Government Policy in Early Childhood Education. Golden Age]: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini. Jeffrey, D. S., & Guido, S. T. (2014). Financing Sustainable Development: Implementing the SDGs through Effective Investment Strategies and Partnerships. Sustainable Development Solutions Network. Juniar, T. (n.d.). Efektivitas Program Kartu Jakarta Pintar (KIP) Dan Manfaatnya Dalam Meningkatkan Kesejahteraan Sosial Di SDN Bintaro 08 Pagi Jakarta Selatan [The Effectiveness of the Jakarta Smart Card (KIP) Program and Its Benefits in Improving Social Welfare at SDN Bintaro 08 Pagi South Jakarta]. Repository.Uinjkt.Ac.Id. Klees, S. J., Ginsburg, M., Anwar, H., Robbins, M. B., Bloom, H., Busacca, C., Corwith, A., Decoster, B., Fiore, A., Gasior, S., Le, H. M., Primo, L. H., & Reedy, T. D. (2020). The World Bank’s SABER: A Critical Analysis. Comparative Education Review. https://doi.org/10.1086/706757 Kurniawati, S., Suryadarma, D., Bima, L., & Yusrina, A. (2018). Education in Indonesia: A white elephant? Journal of Southeast Asian Economies, 35(2), 185–199. https://doi.org/10.1355/ae35-2e Magnuson, K., & Duncan, G. J. (2016). Can early childhood interventions decrease inequality of economic opportunity? Rsf, 2(2), 123–141. https://doi.org/10.7758/rsf.2016.2.2.05 Mizwar Hasyim, N. (2019). Peningkatan Kemandirian Desa Panggungharjo Melalui Komunikasi Pembangunan [Increasing the Independence of Panggungharjo Village through Development Communication]. Jurnal Pemberdayaan Masyarakat: Media Pemikiran Dan Dakwah Pembangunan, 3(2), 352–376. https://doi.org/10.14421/jpm.2019.032-06 Nakajima, N., Hasan, A., Jung, H., Kinnell, A., Maika, A., & Pradhan, M. (2021). Built to Last: Sustainability of Early Childhood Education Services in Rural Indonesia. Journal of Development Studies, 57(10), 1593–1612. https://doi.org/10.1080/00220388.2021.1873283 National Academies of Sciences Engineering and Medicine. (2018). Transforming the Financing of Early Care and Education. In Transforming the Financing of Early Care and Education. The National Academies Press. https://doi.org/10.17226/24984 Penner, E. K., Rochmes, J., Liu, J., Solanki, S. M., & Loeb, S. (2019). Differing views of equity: How prospective educators perceive their role in closing achievement gaps. Rsf, 5(3), 103–127. https://doi.org/10.7758/RSF.2019.5.3.06 Pratama, R. N., & Pambudi, A. (2017). Kinerja Badan Usaha Milik Desa Panggung Lestari dalam Meningkatkan Pendapatan Asli Desa di Desa Panggungharjon Kecamatan Sewon Kabupaten Bantul [Performance of Panggung Lestari Village-Owned Enterprises in Increasing Village Original Income in Panggungharjon Village, Sewon District, Bantul Regency]. Adinegara. Sayre, R. K., Devercelli, A. E., Neuman, M. J., & Wodon, Q. (2015). Investing in Early Childhood Development: Review of the World Bank’s Recent Experience. In Investing in Early Childhood Development: Review of the World Bank’s Recent Experience. https://doi.org/10.1596/978-1-4648-0403-8 Scheerens, J. (2015). School Effectiveness Research. In International Encyclopedia of the Social & Behavioral Sciences: Second Edition (Second Edition, Vol. 21). Elsevier. https://doi.org/10.1016/B978-0-08-097086-8.92080-4 Suryadarma, D., & Jones, G. W. (2013). Education in Indonesia. Education in Indonesia, 39(3), 1–278. The World Bank. (2013). What Matters Most for Early Childhood Development: A Framework Paper. Systems Approach for Better Education Results (SABER) Working Paper Series, 4–59. Vegas, E., & Santibanez, L. (2009). The Promise of Early Childhood Development in Latin America. In The Promise of Early Childhood Development in Latin America. https://doi.org/10.1596/978-0-8213-7759-8 Zúñiga, N. (2018). U4 Anti-Corruption Helpdesk Does: Does more transparency improve accountability? Transparancy International, 1–13.